Clinician-educators in emerging graduate medical education systems: description, roles and perceptions. Issue 1083 (28th October 2015) - Ibrahim, Halah; Stadler, Dora J; Archuleta, Sophia; Shah, Nina G; Bertram, Amanda; Chandrasekhar Nair, Satish; Alkhal, Abdullatif; Ali Al-Mohammed, Ahmed; Cofrancesco, Joseph
Abstract: Objectives: To describe clinician-educators (CEs) in new graduate medical education (GME) systems and characterize perception of preparedness, roles and rewards, and factors affecting job satisfaction and retention. Methods: A cross-sectional survey of all CEs of institutions using competency-based GME and accredited by the Accreditation Council for Graduate Medical Education-International (ACGME-I). Results: 274 of 359 eligible participants (76.3%) responded, representing 47 residency programs across 17 specialties. CEs were predominantly married men aged in their 40s, employed at their current institution 9.3 years (±6.4 years). CEs judged themselves competent or expert in teaching skills (91.5%), trainee assessment (82%) and mentoring (75%); less so in curriculum development (44%) and educational research skills (32%). Clinical productivity was perceived by the majority (62%) as the item most valued by their institutions, with little or no perceived value for teaching or educational efforts. Overall, 58.3% were satisfied or very satisfied with their roles, and 77% expected to remain in academic medicine for 5 years. A strong negative correlation was found between being a program or associate program director and likelihood of staying in academic medicine (aOR 0.42; 0.22 to 0.80). Conclusions: In the GME systems studied, CEs, regardless of country or programme, report working in environments that value clinical productivity over educational efforts. CEs feel competent and prepared for many aspects of their roles, have positive attitudes towards teaching, and report overall job satisfaction, with most likely to remain in academic medicine. As medical training advances internationally, the impact on and by CEs requires ongoing attention.